2021
DOI: 10.1136/bmj.n1088
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of the Pfizer-BioNTech and Oxford-AstraZeneca vaccines on covid-19 related symptoms, hospital admissions, and mortality in older adults in England: test negative case-control study

Abstract: Objective To estimate the real world effectiveness of the Pfizer-BioNTech BNT162b2 and Oxford-AstraZeneca ChAdOx1-S vaccines against confirmed covid-19 symptoms (including the UK variant of concern B.1.1.7), admissions to hospital, and deaths. Design Test negative case-control study. Setting Community testing for covid-19 in England. Participants 156 930 adults a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

48
727
7
17

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,024 publications
(799 citation statements)
references
References 19 publications
48
727
7
17
Order By: Relevance
“…These results are in line with the real-world efficacy of the two vaccines. The Pfizer vaccine is known to be protective against asymptomatic and symptomatic infections, including severe diseases, induced by B.1.1.7 and B.1.351, as described for instance in the UK, Israel and South Africa [46][47][48] In contrast, the efficacy of a two-dose regimen of AstraZeneca against mild-to-moderate disease dropped to 10% in South Africa, where the B.1.351 variant circulates 49 . Altogether, our results suggest that a single dose of AstraZeneca vaccine will not display an optimal protection against B.1.617.2.…”
Section: Sensitivity Of B16172 To Sera From Vaccine Recipientsmentioning
confidence: 99%
“…These results are in line with the real-world efficacy of the two vaccines. The Pfizer vaccine is known to be protective against asymptomatic and symptomatic infections, including severe diseases, induced by B.1.1.7 and B.1.351, as described for instance in the UK, Israel and South Africa [46][47][48] In contrast, the efficacy of a two-dose regimen of AstraZeneca against mild-to-moderate disease dropped to 10% in South Africa, where the B.1.351 variant circulates 49 . Altogether, our results suggest that a single dose of AstraZeneca vaccine will not display an optimal protection against B.1.617.2.…”
Section: Sensitivity Of B16172 To Sera From Vaccine Recipientsmentioning
confidence: 99%
“…Evidence on the safety of COVID-19 vaccines continue to emerge, a larger prospective observational studies in a country like United Kingdome with mass vaccination campaigns showed lower frequencies of adverse effects than reported in phase III trials [ 15 ]. Real world data in elderly patients have also shown safety and efficacy of both AstraZeneca and Pfizer COVID-19 vaccines [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Toute décision prise doit tenir compte de la balance bénéfice-risque qui est largement en faveur de tous les vaccins disponibles à ce jour. Leur efficacité, comme l'ont montré les recherches menées tant en Europe qu'aux Etats-Unis, est, par définition, supérieure à cinquante pour cent 34 . En conséquence, le vaccin d'AstraZeneca a été stigmatisé et des patients qui ne savent rien du plus simple calcul risque-bénéfice réclament maintenant le droit de choisir leurs vaccins 35 .…”
Section: Médecine De Catastropheunclassified